Analysis of incomplete and complete contacts in sliding and partial slip - Karuppanan, S (2008)
Fretting fatigue is a type of contact fatigue which causes premature failure in a number of engineering assemblies subjected to vibration or other forms of cyclic loading. It is concerned with the nucleation of cracks due to oscillatory micro slip between contacting bodies. Therefore, a detailed knowledge of the interface conditions and the means of quantifying crack nucleation are very important, and will be the ultimate goal of this thesis. The analysis of an incomplete contact (Herzian contact) is considered first followed by various complete contacts. Fretting fatigue tests employing a Hertzian contact are analysed accurately by introducing several modifications needed to the classical formulation. With the total state of stress in a strip established, the crack tip stress intensity factor for a crack growing inward from the trailing edge of the contact is determined by the distributed dislocation technique. The results are then correlated with local solutions for the contact stress field which enable an estimate of the crack nucleation life, and hence a characteristic material property quantifying initiation, to be found. The interfacial contact pressure distribution beneath a complete sliding contact between elastically similar components, in the presence of friction, has been studied in detail, with particular reference to contacts whose edge angles are 60 degree, 90 degree and 120 degree. The possible types of behaviour at the edge of contacts, namely power order singularity, power order bounded and square root bounded, are discussed. A full understanding of the behaviour requires a detailed study of a characteristic equation, and this shows the kinds of pressure distribution to be anticipated, which can vary very markedly. The transition from power order behaviour to local separation and bounded behaviour is examined, and an appropriate asymptotic form developed. The problem of trapezium shaped punches pressed into a frictional, elastically similar half-plane, and subject to sequential normal and shear loading, under partial slip, is studied. Detailed considerations have again been given to the specific cases of 60 degree, 90 degree and 120 degree punches, and maps have been developed showing the initial mix of stick, slip and separation regions, together with the steady state response when the shearing force is cycled. Conditions for full stick are established.